2015
DOI: 10.1007/s11356-015-5499-y
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation patterns of Cr in Callitriche organs—qualitative and quantitative analysis

Abstract: The aims of this study were both the qualitative and quantitative analysis of chromium accumulation in the shoots of Callitriche cophocarpa. This globally distributed, submersed macrophyte exhibits outstanding Cr phytoremediation capacity in an aquatic environment. Cr was applied separately for 7 days at two stable forms as Cr(VI) and Cr(III), known from their diverse physicochemical properties and toxicities. The maps of Cr depositions in young leaves, mature leaves, and stems were obtained by micro X-ray flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
3
4
0
Order By: Relevance
“…At first, a 3-h treatment was examined, which revealed direct reaction to Cr(VI) by strongly increasing CAT and peroxidase activities. This early-response stage (an alarm phase of plant response as indicated by Kosová et al 2011 ) is consistent with our previous observations which showed immediate reaction of C. cophocarpa shoots treated with chromate and manifested by a rapid (in a matter of hours) reduction of Cr(VI) to the Cr(V) intermediate which is generated upon Cr(VI) → Cr(III) bioconversion (Augustynowicz et al 2013a , 2016 ). During prolonged (3-day) incubation, only Px activities were kept elevated while CAT was back at the level determined for control plants.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…At first, a 3-h treatment was examined, which revealed direct reaction to Cr(VI) by strongly increasing CAT and peroxidase activities. This early-response stage (an alarm phase of plant response as indicated by Kosová et al 2011 ) is consistent with our previous observations which showed immediate reaction of C. cophocarpa shoots treated with chromate and manifested by a rapid (in a matter of hours) reduction of Cr(VI) to the Cr(V) intermediate which is generated upon Cr(VI) → Cr(III) bioconversion (Augustynowicz et al 2013a , 2016 ). During prolonged (3-day) incubation, only Px activities were kept elevated while CAT was back at the level determined for control plants.…”
Section: Discussionsupporting
confidence: 91%
“…Plants were grown in a phytotron chamber (model FD 500, Biosell, Poland) under the following conditions: 16 h of photon flux density of 40 μmol m −2 s −1 and 8 h of darkness, at 22-°C day/18-°C night. Light spectrum and intensity were similar to that applied in previous studies (Augustynowicz et al 2016 ) and were found sufficient for normal plant growth resembling the conditions typical of Callitriche natural environment.…”
Section: Methodssupporting
confidence: 80%
See 3 more Smart Citations